Influence of friction stir welding process and tool parameters on strength properties of AA7075-T 6 aluminium alloy joints - Rajakumar, S.; Muralidharan, C.; Balasubramanian, V. (Materials in engineering, 2011)
The aircraft aluminium alloys generally present low weldability by traditional fusion welding process. The development of the friction stir welding has provided an alternative improved way of satisfactorily producing aluminium joints, in a faster and reliable manner. In this present work, the influence of process and tool parameters on tensile strength properties of AA7075-T 6 joints produced by friction stir welding was analysed. Square butt joints were fabricated by varying process parameters and tool parameters. Strength properties of the joints were evaluated and correlated with the microstructure, microhardness of weld nugget. From this investigation it is found that the joint fabricated at a tool rotational speed of 1400 rpm, welding speed of 60 mm/min, axial force of 8 kN, using the tool with 15 mm shoulder diameter, 5 mm pin diameter, 45 HRc tool hardness yielded higher strength properties compared to other joints.